Oscillation criteria for perturbed half-linear differential equations - Manabu Naito (Electronic Journal of Qualitative Theory of Differential Equations)
Oscillatory properties of perturbed half-linear differential equations are investigated. We make use of the modified Riccati technique. A certain linear differential equation associated with the modified Riccati equation plays an important part. Improved oscillation criteria for a perturbed half-linear Riemann–Weber differential equation can be obtained.